2014
DOI: 10.1186/cc13982
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous thrombin potential following hemostatic therapy with 4-factor prothrombin complex concentrate: a 7-day observational study of trauma patients

Abstract: IntroductionPurified prothrombin complex concentrate (PCC) is increasingly used as hemostatic therapy for trauma-induced coagulopathy (TIC). However, the impact of PCC administration on coagulation status among patients with TIC has not been adequately investigated.MethodsIn this observational, descriptive study, data relating to thrombin generation were obtained from plasma samples gathered prospectively from trauma patients upon emergency room (ER) admission and over the following 7 days. Standard coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 67 publications
3
63
0
2
Order By: Relevance
“…For example, there are no studies looking at the effect of modern treatment on the rate of post-trauma venous thromboembolism, which is a major cause of morbidity and mortality. It is recognised that the use of prothrombin complex concentrate may induce later prothrombotic changes [91], and potentially this may affect the rate of posttrauma thromboembolism.…”
Section: The Evolving Importance Of Atc In Trauma Resuscitationmentioning
confidence: 99%
“…For example, there are no studies looking at the effect of modern treatment on the rate of post-trauma venous thromboembolism, which is a major cause of morbidity and mortality. It is recognised that the use of prothrombin complex concentrate may induce later prothrombotic changes [91], and potentially this may affect the rate of posttrauma thromboembolism.…”
Section: The Evolving Importance Of Atc In Trauma Resuscitationmentioning
confidence: 99%
“…Several European centres have incorporated PCC into POC guided algorithms in view of the potential benefits of low volume delivery of a potent thrombin generator without excess thromboembolic events [79,95] . In trauma patients, concerns remain about the sustained prothrombotic potential for up to 4 d post PCC administration [107] . In light of evidence for perioperative hypercoagulability in some patients with liver disease the prothrombotic potential of PCC should not be dismissed [108][109][110] .…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…Joseph et al reported an incidence of thromboembolic events in the range of 6% after prothrombin complex concentrate administration in a heterogeneous group of trauma patients [82]. Our group showed recently that prothrombin complex concentrate administration resulted in a substantial and prolonged increase in endogenous thrombin generation compared with patients who received no coagulation therapy or fibrinogen concentrate only [83]. The recent European guidelines for massive trauma-related bleeding recommend administration of prothrombin complex concentrate primarily for the emergency reversal of vitamin K-dependent oral anticoagulation.…”
Section: Improvement In Thrombin Generationmentioning
confidence: 69%
“…BGA, blood gas analysis; BW, body weight; CT, clotting time; FFP, fresh frozen plasma; ISS, injury severity score; ML, maximum lysis; PC, platelet concentrate; PCC, prothrombin complex concentrate; TXA, tranexamic acid Severity Classification Score and the Trauma Injury Severity Score [80]. Another study by the same group showed that coagulation therapy based on fibrinogen concentrate and prothrombin complex concentrate was associated with less frequent exposure to allogeneic blood products compared with patients who received FFP, but had no effect on mortality [81].…”
Section: Improvement In Thrombin Generationmentioning
confidence: 99%